Validity of the International Fitness Scale (IFIS) and its associations with cardiometabolic health and body composition in adults with type 2 diabetes: A cross-sectional study - Ángel Herraiz-Adillo; Karin Rådholm; Fredrik Iredahl; Carl-Johan Carlhäll; Nahuel Roemkens; Mikael Forsgren; Olof Dahlqvist Leinhard; Peter Lundberg; Stergios Kechagias; Nils Dahlström; Patrik Nasr; Mattias Ekstedt; et al. (PLoS ONE, 2026)
Aims To assess the validity of the International Fitness Scale (IFIS) for evaluating cardiorespiratory fitness compared to the 6-minute walk test (6MWT) (criterion validity) and to examine associations with cardiometabolic and body composition outcomes (construct validity). Methods A cross-sectional analysis was conducted on 282 adults with type 2 diabetes mellitus (T2DM) (mean age 63.6 ± 8.1 years, 37.9% women). Self-reported fitness was assessed using IFIS, including overall, cardiorespiratory, muscular, speed-agility and flexibility scores. Objective cardiorespiratory fitness was assessed using the 6MWT. Associations with 6MWT, cardiometabolic (i.e., cardiovascular health score, metabolic dysfunction-associated steatotic liver disease [MASLD], high-sensitivity C-reactive protein) and body composition outcomes (i.e., body mass index [BMI], visceral adipose tissue volume, thigh fat-free muscle volume) were analyzed using ANCOVA (adjusted by sex and age) and ROC curves, compared using DeLong tests. Results Both IFIS overall and IFIS cardiorespiratory showed graded associations with 6MWT (p < 0.001 for ANCOVA models). For discriminating performance below the population-predicted mean 6MWT distance, IFIS cardiorespiratory showed an AUC of 0.615 (95% CI: 0.552–0.678). Apart from IFIS muscular, IFIS scores were significantly associated with all cardiometabolic and body composition outcomes, with ROC analyses showing at least similar predictive performance for IFIS overall and cardiorespiratory fitness scores compared to 6MWT. Notably, IFIS overall outperformed the 6MWT for predicting poor cardiovascular health (AUCs: 0.678 [95% CI: 0.618–0.737] versus 0.586 [95% CI: 0.517–0.654]) and MASLD (AUCs: 0.630 [95% CI: 0.563–0.696] versus 0.519 [95% CI: 0.443–0.595]). Conclusion This study supports that IFIS may be a practical tool for adults with T2DM, showing evidence of criterion validity via graded association with 6MWT performance, and construct validity via significant associations with cardiometabolic and body composition outcomes. Although its ability to discriminate impaired functional capacity was limited, IFIS may serve as a feasible alternative for fitness assessment when objective testing is not possible in primary care.